Imaging in blunt cardiac injury: Computed tomographic findings in cardiac contusion and associated injuries. Issue 5 (May 2016) - Hammer, Mark M.; Raptis, Demetrios A.; Cummings, Kristopher W.; Mellnick, Vincent M.; Bhalla, Sanjeev; Schuerer, Douglas J.; Raptis, Constantine A.
Abstract: Background: Blunt cardiac injury (BCI) may manifest as cardiac contusion or, more rarely, as pericardial or myocardial rupture. Computed tomography (CT) is performed in the vast majority of blunt trauma patients, but the imaging features of cardiac contusion are not well described. Purpose: To evaluate CT findings and associated injuries in patients with clinically diagnosed BCI. Materials and methods: We identified 42 patients with blunt cardiac injury from our institution's electronic medical record. Clinical parameters, echocardiography results, and laboratory tests were recorded. Two blinded reviewers analyzed chest CTs performed in these patients for myocardial hypoenhancement and associated injuries. Results: CT findings of severe thoracic trauma are commonly present in patients with severe BCI; 82% of patients with ECG, cardiac enzyme, and echocardiographic evidence of BCI had abnormalities of the heart or pericardium on CT; 73% had anterior rib fractures, and 64% had pulmonary contusions. Sternal fractures were only seen in 36% of such patients. However, myocardial hypoenhancement on CT is poorly sensitive for those patients with cardiac contusion: 0% of right ventricular contusions and 22% of left ventricular contusions seen on echocardiography were identified on CT. Conclusion: CT signs of severe thoracic trauma are frequently present in patients with severe BCI and should be regarded as indirect evidence of potential BCI. Direct CT findings of myocardial contusion, i.e. myocardial hypoenhancement, are poorly sensitive and should not be used as a screening tool. However, some left ventricular contusions can be seen on CT, and these patients could undergo echocardiography or cardiac MRI to evaluate for wall motion abnormalities.